Demographic profile, pattern, practice of energy drink and substance use among undergraduate students in BPKIHS - Kushwaha, Ramayan Prasad; Mandal, Namita Kumari; Koirala, Bhawesh; Rauniar, Gajendra Prasad (Asian Journal of Medical Sciences, 2019)
Background: The consumption of caffeinated energy drinks is a common practice among college students. Energy drinks are believed to increase energy, stamina, wakefulness, and reduce hangover symptoms. Aims and Objective: This study aims to find out the profile, pattern, practice of energy drink and substance use among undergraduate students in BP Koirala Institute of Health Sciences. Materials and Methods: It was a self-reported questionnaire based descriptive cross-sectional study. The questionnaire included demographic details, patterns of energy drink used, mixing practice of alcohol with energy drinks or other beverages, substance use behavior, and the knowledge about the main constituents of energy drinks. Alcohol mixing practice was further categorized into a) Alcohol + Energy drink mixing group, b) Alcohol + Other beverages mixing group, c) Only Alcohol group. Results: Out of 319 students, 188 (58.9%) were male. The prevalence of energy drink use was 186 (58.3%). Red Bull (176, 94.6%) was the most preferred energy drink. The use of alcohol (29, 87.9%), tobacco (20, 60.6%), and marijuana (13, 39.4%) was more prevalent in students using energy drinks on a daily basis. Thirty percent (57) alcohol user students were mixed alcohol with energy drink among them 42 (73.7%) used tobacco and 24 (42.1%) used marijuana. Conclusion: The overall energy drinks use among the students was high. The occurrence of various substance misuse was more among those students who consumed energy drink more frequently or consumed it with alcohol. Frequent consumption of energy drinks alone or mix with alcohol is not recommended.